2004
DOI: 10.1080/07315724.2004.10719400
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium VitB6 Intake Reduces Central Nervous System Hyperexcitability in Children

Abstract: This open study indicates that hyperexcitable children have low ERC-Mg with normal serum Mg(2+) values, and that Mg(2+)/vitamin B6 supplementation can restore normal ERC-Mg levels and improve their abnormal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 6 publications
3
35
0
2
Order By: Relevance
“…The essential role of zinc in protein and nucleic acid syntheses has also been proven (19)(20)(21). Magnesium plays a fundamental role in the energy-production conversion of ATP to ADP (22).…”
Section: Introductionmentioning
confidence: 99%
“…The essential role of zinc in protein and nucleic acid syntheses has also been proven (19)(20)(21). Magnesium plays a fundamental role in the energy-production conversion of ATP to ADP (22).…”
Section: Introductionmentioning
confidence: 99%
“…Our results (Mousain--Bosc et al, 2004) showed a statistically significant improvement of the symptoms after Mg--B6 supplementation, together with a rise in Erc--Mg values. In this study, a slight but significant intra--erythrocyte Mg depletion was evident in ADHD patients together with a concomitant decrease in intracellular calcium concentrations.…”
Section: Experimental Study Numbersupporting
confidence: 57%
“…Other studies from Kozielec et al, for the first time reported an intra--erythrocyte magnesium deficiency in ADHD children . We also published similar data (Mousain--Bosc et al, 2004. However, it is not a true "Mg deficiency" with clinically associated respiratory repletion, as is observed in familial hypomagnesaemia with secondary hypocalcemia (Shalev et al, 1998;Mousain--Bosc et al, 2004).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…■ Неврологические роли магния осуществляются при участии иона Mg2+ в синаптической передаче сигнала с участием допамина, NMDA-рецепторов, в многочислен-ных сигнальных путях опосредования эффектов других нейротрансмиттеров (сигнальных G(s)-, G(i)-и G(z)-белков, ионов кальция, фосфолипазы С, которые участвуют в осу-ществлении эффектов катехоламинов, серотонина, до-памина и др.). Нарушение активности этих белков будет приводить к дефициту внимания и гиперактивности, ко-морбидных дефициту магния [4,[15][16][17]. При этом при де-фиците витамина В6 будет наблюдаться дефицит нейро-трансмиттеров, который проявится у детей в задержке развития, у детей и взрослых -в дисфункции перифери-ческой нервной системы, гипотония и гипокинезия [18].…”
Section: табл 2)unclassified